Women in audio - Gaston-Bird, Leslie, 1969- (Audio Engineering Society presents., 2019)
Women in Audio features almost 100 profiles and stories of audio engineers who are women and have achieved success throughout the history of the trade. Beginning with a historical view, the book covers the achievements of women in various audio professions andthen focuses on organizations that support and train women and girls in the industry. What follows are eight chapters divided by discipline, highlighting accomplished women in various audio fields: radio; sound for film and television; music recording and electronic music; hardware and software design; acoustics; live sound and sound for theater; education; audio for games, virtual reality, augmented reality, and mixed reality, as well as immersive sound. Women in Audio is a valuable resource for professionals, educators, and students looking to gain insight into the careers of trailblazing women in audio-related fields and represents required reading for those looking to add diversity to their music technology programs.